2014
DOI: 10.1093/infdis/jiu060
|View full text |Cite|
|
Sign up to set email alerts
|

Switch From Oral to Inactivated Poliovirus Vaccine in Yogyakarta Province, Indonesia: Summary of Coverage, Immunity, and Environmental Surveillance

Abstract: This project demonstrated that under almost ideal conditions (good hygiene, maintenance of universally high IPV coverage, and corresponding high immunity against polioviruses), no emergence and circulation of VDPV could be detected in a tropical developing country setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
3
29
1
Order By: Relevance
“…Previous studies have reported a rapid decline in PV isolation around the OPV-to-IPV transition period, with a disappearance of PV vaccine strains from wastewater within 2 to 3 months after the cessation of OPV administration (40)(41)(42)(43). In contrast, our study showed the disappearance of Sabin-like PVs from the environment before OPV immunization had ceased (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies have reported a rapid decline in PV isolation around the OPV-to-IPV transition period, with a disappearance of PV vaccine strains from wastewater within 2 to 3 months after the cessation of OPV administration (40)(41)(42)(43). In contrast, our study showed the disappearance of Sabin-like PVs from the environment before OPV immunization had ceased (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…The frequency of SL2 detection in both BMFS and twophase samples can provide an important baseline to compare SL2 prevalence and persistence after the switch from trivalent OPV to bivalent OPV. The frequency of SL2 detection was comparable to other settings (Esteves-Jaramillo et al 2014;Nakamura et al 2015;Wahjuhono et al 2014;Wang et al 2014). This may be due to the high rate of PV2 shedding (88%), compared to PV1 (42%) and PV3 (58%) shedding 1 week after OPV use (Laassri et al 2005) as demonstrated by frequent PV2 detection within 3 weeks after OPV use (n = 10) compared to prior to OPV use (n = 32) (SL1: 40% vs. 38%, SL2: 90% vs. 84%, and SL3: 60% vs. 59% in BMFS and two-phase samples, respectively).…”
Section: Virus Detectionsupporting
confidence: 70%
“…On the other hand, Yogyakarta in Indonesia also switched to an all IPV schedule and has not detected any VDPVs since the change [50]. Yogyakarta had very high coverage and improved economic and public health infrastructure which may limit generalizability of this case to the low-income settings.…”
Section: End Game Barriersmentioning
confidence: 92%